Physician assistants in Australasian emergency departments. (19th May 2016) - Close, Benjamin; Zolcinski, Robert
Abstract: A physician assistant (PA) is a university qualified health professional who's primary role is to provide medical care under the direction and supervision of medical staff. This is a new profession in Australasia. The PA is well suited to working in both rural, regional and urban settings that deliver emergency medical care. A perspective is presented on their role and scope of practice within the Australasian emergency care system supported by some early findings from their use in a tertiary ED.